A review on hospital wastewater treatment: A special emphasis on occurrence and removal of pharmaceutically active compounds, resistant microorganisms, and SARS-CoV-2. Issue 2 (April 2021) - Majumder, Abhradeep; Gupta, Ashok Kumar; Ghosal, Partha Sarathi; Varma, Mahesh
Abstract: The hospital wastewater imposes a potent threat to the security of human health concerning its high vulnerability towards the outbreak of several diseases. Furthermore, the outbreak of COVID-19 pandemic demanded a global attention towards monitoring viruses and other infectious pathogens in hospital wastewater and their removal. Apart from that, the presence of various recalcitrant organics, pharmaceutically active compounds (PhACs), etc. imparts a complex pollution load to water resources and ecosystem. In this review, an insight into the occurrence, persistence and removal of drug-resistant microorganisms and infectious viruses as well as other micro-pollutants have been documented. The performance of various pilot/full-scale studies have been evaluated in terms of removal of biochemical oxygen demand (BOD), chemical oxygen demand (COD), total suspended solids (TSS), PhACs, pathogens, etc. It was found that many biological processes, such as membrane bioreactor, activated sludge process, constructed wetlands, etc. provided more than 80% removal of BOD, COD, TSS, etc. However, the removal of several recalcitrant organic pollutants are less responsive to those processes and demands the application of tertiary treatments, such as adsorption, ozone treatment, UV treatment, etc. Antibiotic-resistant microorganisms, viruses were found to be persistent even after the treatment of hospital wastewater, and high dose of chlorination or UV treatment was required to inactivate them. This article circumscribes the various emerging technologies, which have been used to treat PhACs and pathogens. The present review also emphasized the global concern of the presence of SARS-CoV-2 RNA in hospital wastewater and its removal by the existing treatment facilities. Graphical Abstract: ga1 Highlights: The organic fraction in hospital wastewater has low biodegradability index. Some bacteria in hospital effluents develop resistance to antibiotics and other drugs. SARS-CoV-2 RNA in wastewater and COVID-19 affected people are positively correlated. CWs and MBR have been efficient in terms of ARG and ARB inactivation. 30–80 mg min/L of chlorine can inactivate various ARG, ARB, and viruses.